The Operational Indicator of "Insani" Resources Criteria As The Implementation of Islamic Human Resource Management - Ah. Ali Arifin; Nurlaili Adkhi Rifza Faiza (AFEBI Management and Business Review, 2019)
Human being has function as Khalifah fil arḍ means that has qualification as man power in maximizing the function of organizing resources. In an organization, the khalifah function is to achieve a maximum results acknowledge as Insani Resources (IR).The aims of this writing are to break down the criteria of Insani to be operatively in strengthening the theory of human resource management. This paper focusing on three criteria of Insani Resources; Al-Qawiy Al-Amīn (QS: [28]: 26), Makīnun Amīnun (Surah: [12]: 54) and Ḥafīẓun Alīmun (Surah: [12]: 55). In sort,  the relevance of Al-Qawiy Al-Amīn, Makīnun Amīnun and Ḥafīẓun Alīmun, that the criteria of IR Al-Qawiy Al-Amīn, Makīnun Amīnun and Ḥafīẓun Alīmun have entered the standard of IR qualification of Islamic economics  Keywords:  Insani Resource (IR), Al-Qawiy Al-Amīn, Makīnun Amīnun, Ḥafīẓun Alīmun.